CURRENT STATE AND PROSPECTS OF SOYBEAN SEED BREEDING IN THE FOREST-STEPPE OF UKRAINE - Biliavska, L. H.; Biliavskyi, Yu. V.; Shapoval, O. S.; Panchenko, S. S. (Scientific Progress & Innovations, 2020)
The article presents the analysis results of the current state of soybean production. Soybean yields in Ukraine have varied between 1.7–2.4 t/ha in recent years (2012–2020). In 2018, there were 138 varieties in the official circulation on seed market in Ukraine. Advanced foreign breeding companies, the portfolio of their modern varieties and prospects for expanding the sown areas under them have been presented. Ukrainian varieties, their genetic potential and yield level in the conditions of insufficient moistening in the Forest-Steppe of Ukraine have been indicated. Changing weather conditions require breeders to select varieties, which are better adapted to certain cultivation conditions, have definite economically valuable characteristics and provide a profitable yield level. Under insufficient moistening, the using of early ripening and very early ripening varieties is relevant. According to the results of the analysis of 17-year meteorological observations it has been established that the climatic characteristics of Poltava region have become more arid. The dynamics of gross soybean yield in Poltava region (2002–2018) has been analyzed taking into account the precipitation amount during the growing season (the 4th – 8th months). Leading Ukrainian seed companies ATK, “Prograin Ukr”, “Astarta-Kyiv”, “Agro-firm-Obrii”, “Zakhidnyi Buh’ have been mentioned. The best foreign and national companies producing soybean seed in Ukraine have been identified (2017–2018). Such companies as Soievyi vik, ISGP of the National Academy of Agrarian Sciences of Ukraine, ISG SZ of the National Academy of Agrarian Sciences of Ukraine, and Poltava State Agrarian Academy of the Ministry of Education and Science of Ukraine have a high rating among the Ukrainian selection centers. But the share of their varieties in the production is gradually decreasing each year. In 2010–2012, the share of soybean areas under varieties of Poltava State Agrarian Academy selection in Poltava region was 4.8–10.4 % of the total areas. At present, under market transformations and innovative processes in the agro-industrial complex, there are problems concerning further strategy of developing and increasing the effectiveness of the national system of seed breeding in Ukraine. The number of certified soybean seed growing farms has significantly decreased in this country. So, there have been only 7 such farms in Poltava region in 2020. On “Hryha” seed growing farm, according to the results of ecological variety testing, it has been established that the varieties bred at Poltava State Agrarian Academy (Adamos, Almaz, Aleksandryt) are highly competitive with the best foreign varieties such as Alligator (2.97 t/ha), ES Navigator (3.07 t/ha), RZhT Stumpa (3.19 t/ha), Furio (2.92 t/ha). A certification model, equal conditions and opportunities have been created for all seed producers in Ukraine. Establishing the status of producer of seeds as a valuable commercial product for further distribution on the Ukrainian market and export to foreign markets has been guaranteed for all seed producers (Ukrainian and foreign).